THE INFLUENCE OF MONITORING SYSTEM AND WORK DISCIPLINE ON EMPLOYEE WORK PRODUCTIVITY AT CV. MAKMUR JAYA, MALANG - Djoni Bahtiar; Is Fadhilah (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to analyze the influence of monitoring system and work discipline on employee work productivity at CV. Makmur Jaya Malang. This study took a sample of 50 employees. Sampling in this study used a saturated or census sampling method because the population was small and limited, namely 50 respondents. The analysis used was multiple regression, using a significance limit of 0.05. The results of this study show two things. First, partially, the monitoring system has a positive and significant effect on employee work productivity and work discipline also has a positive and significant effect on employee work productivity at CV. Makmur Jaya Malang. Second, simultaneously, the monitoring system and work discipline together have a significant effect on employee work productivity at CV. Makmur Jaya Malang.